United Kingdom’s Strategy in Responding Foreign Terrorist Fighters Returnees from Syria Conflict in 2018-2022 - Yasmine, Aura Firdausi; Effendi, Yusli (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
The increasing number of British Foreign Terrorist Fighters (FTF) Returnees from Syria demanded a special response from Britain’s Government, compared to their previous ones. Britain with their infamous liberal values, without hesitation has abandoned certain limitations to liberty and human rights in order to protect their country from extremism carried by FTF returnees, by treating them as extraordinary criminals. Through literature study and Criminal Justice Model theory, this research identifies the contents in United Kingdom’s (UK) Counter Terrorism Strategy (CONTEST), UK government’s report, as well as independent review, and found that Britain’s counter terrorism is predominantly used on a domestic level, mainly pushing the implementation of Temporary Exclusion Orders (TEO) and Prevent Duty. The UK has proven that they are not fully bound to the liberal values and is also capable of enforcing state violence as an effort against terrorism. Since they are dealing with FTF returnees this time, who are ultimately the citizens of Britain, their counterterrorism efforts deal significantly with inward looking measures instead of global or international. These measures include controlling an alleged FTF returnee movement on their way home, and also stripping the rights to travel, residence, and movement. Although considered to be a comprehensive strategy, another outcome of the UK's form of counterterrorism is the unwanted generalization of the British muslim community.